Toward More Equitable Instruction: How Teachers Integrate Ambitious, Traditional, and Culturally Responsive Mathematics Practices - Meghan Comstock; Kenneth A. Shores; Erica Litke; Laura M. Desimone; Camila Polanco; Kirsten Lee Hill (AERA Open)
Increasingly, there is consensus that equitable mathematics instruction incorporates ambitious and culturally responsive (CR) practices. Using self-reported survey data and mixture modeling, we examine teachers’ emphasis on ambitious, traditional, and CR mathematics practices. We offer an emergent typology for characterizing teacher engagement with CR teaching in mathematics. One-half of teachers—predominantly White and experienced—reported rarely engaging in CR practices, focusing exclusively on a mix of ambitious and traditional practices. One-third of teachers emphasized some CR practices alongside ambitious and traditional practices. Less than one-quarter of teachers—predominantly teachers of color—emphasized ambitious mathematics and a robust set of CR practices. Teachers who de-emphasize CR teaching reported believing in it but having low self-efficacy. We offer implications for policy and practice.